The BRICs, US ‘Decline’ and Global Transformations - Kiely, R. author. aut Link
IX, 243 p.
Keywords: The author examines the rise of the BRICs and the supposed decline of the United States. Focusing on the boom years from 1992 to 2007, and the crisis years after 2008, he argues that there are limits to the rise of the former and that the extent of US decline has been greatly exaggerated.